Beyond Patriarchy: Eco-Masculinity as an Alternative Masculine Identity in Perumal Murugan’s One Part Woman - Binola J; Dr. A. Annie Divya Mahisha (ILN Journal: Indian Literary Narratives, 2025)
This article explores the concept of eco-masculinity as an alternative framework to understand masculine identities, with a focus on Perumal Murugan’s One Part Woman. Traditional patriarchal norms define masculinity through domination, virility, and reproductive success, marginalizing men who do not conform. Eco-masculinity, on the other hand, emphasizes the value of caring, reciprocity, and the interconnectedness of men, land, and non-human life as legitimate manifestations of masculinity. This alternative approach is best illustrated by the character Kali, whose masculinity is based on his closeness to the earth, his compassion for cattle and his synchronization with ecological cycles. While society ridicules him for his infertility and forces his wife into coercive rituals of reproduction, his dignity emerges from ecological stewardship and emotional vulnerability. Through this lens, Kali’s woundedness is exposed as the result of patriarchal erasure of alternative masculinity rather than as a personal weakness. Eco-masculinity not only challenges the violence of patriarchal systems but also gestures toward sustainable, ethical models of manhood that affirm both human and ecological survival. By reading One Part Woman, this paper argues that eco-masculinity provides a transformative framework that redefines masculine identities beyond patriarchal binaries, making space for tenderness, ecological consciousness, and ethical coexistence.